Pemberdayaan Masyarakat Gampong Jawa Melalui Budidaya Sorgum & Diversifikasi Olahannya Sebagai Makanan Sehat Bergizi - Ainul Mardiyah; Cut Mulyani; Cut Gustiana (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
Community service is carried out by raising the topic of cultivation and diversification of sorghum flour processing. Sorghum is a cereal plant that is not as familiar as rice, corn, and wheat. Sorghum cultivation in today's society is very rarely done, especially in densely populated areas with less land availability. However, this does not become an obstacle to the introduction and cultivation of sorghum in the community. Gampong Jawa is an area with a population density exceeding 50 families and the availability of agricultural land is very less. Organic sorghum cultivation technique is an alternative that can be tried to introduce sorghum and the benefits of this plant in the community. Residents' yards are an alternative to sorghum farming. The guidance for this activity includes organic sorghum cultivation techniques using liquid hormone fertilizer, plant maintenance, to processing seeds into flour and into biscuit products that are rich in fiber and nutrients. The service is planned to be carried out for 3 months in the field and 1 month in making publications and reporting.